Philo, Writer of History: Constructing a Transcultural Literary Context in De vita Mosis - Moolenburgh, Maarten-Pieter S. (Histos)

(untitled) (University of Alberta Library, 2026)
Whereas most scholarship interprets Philo’s De vita Mosis as a biography or encomium written in the context of a polemic about Judaism, this article proposes instead that the work serves to establish Philo more broadly as an authoritative Graeco-Roman writer of history. To this end, I analyse Philo’s comments about his literary competitors in the proem, his use of historiographical genre conventions, and his engagement with contemporary literary criticism; further corroboration is provided by his comments about the Mosaic Pentateuch in the second book. This article thus provides a foundation to consider De vita Mosis in relation to Graeco-Roman historical writing in its full breadth.